2007
DOI: 10.3382/ps.2007-00265
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Broiler Breeder Genetic Strain and Parent Flock Age on Eggshell Conductance and Embryonic Metabolism

Abstract: The effect of genetic strain (Ross 308; Cobb 500) and parent flock age [young (29 wk), peak (Ross = 34 wk; Cobb = 36 wk), postpeak (40 wk), mature (45 wk), old (55 wk), and very old (59 wk)] on eggshell conductance and embryonic metabolism were examined. At each flock age, eggs from each strain were incubated for 21.5 d in individual metabolic chambers to measure embryonic O(2) intake and CO(2) output. From these data, the respiratory quotient (RQ) and metabolic heat production were calculated. Data were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 13 publications
0
42
1
1
Order By: Relevance
“…The metabolic rate of layer embryos from the older breeder flock used in the previous study was 30% lower than in embryos produced by the peak breeder flock used in the current work (9 mL * h −1 versus 13 mL * h −1 ) [7]. It has previously been reported that egg shell conductance and porosity decrease as a breeder flock ages [21]. If this is the case, it can be speculated that the decrease in shell porosity possibly reduced the O 2 diffusion capacity of the shell pore system and the resultant hypoxia limited metabolism in the old breeder flock [5].…”
Section: Metabolic Ratecontrasting
confidence: 49%
“…The metabolic rate of layer embryos from the older breeder flock used in the previous study was 30% lower than in embryos produced by the peak breeder flock used in the current work (9 mL * h −1 versus 13 mL * h −1 ) [7]. It has previously been reported that egg shell conductance and porosity decrease as a breeder flock ages [21]. If this is the case, it can be speculated that the decrease in shell porosity possibly reduced the O 2 diffusion capacity of the shell pore system and the resultant hypoxia limited metabolism in the old breeder flock [5].…”
Section: Metabolic Ratecontrasting
confidence: 49%
“…According to the literature, increased residual yolk is a sign of overheating (LEKSRISOMPONG et al, 2007), which reaffirms the possibility that non-scheduled variations at inadequate times may negatively affect normal development. In the industry, temperature variability in different regions of the machine is often observed (FRENCH, 2002), since there are eggs of various origins and in different phases of development, in addition to differences in metabolism, oxygen consumption, and size due to breeder hens of different ages (LOURENS et al, 2006;HAMIDU et al, 2007). This study evaluated the development of embryos from Ross ® breeder hens aged between 61 and 63 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Conductance is the capacity of gas exchange between the egg and the environment, and it is related with water (Campos et al, 2003) and metabolic heat (Hamidu et al, 2007) losses. The higher the egg conductance and the water loss, the higher egg heat loss by evaporation.…”
Section: Discussionmentioning
confidence: 99%